«Il libro della vera sapienza». Francesco Puccinotti lettore delle Operette morali - Colombo, Paolo (Rivista Internazionale di Studi Leopardiani, 2023)
The essay intends to present the results of a broader ongoing research dedicated to the ‘leopardian’ doctor Francesco Puccinotti (1794-1872), focusing on the predilection he constantly professed, up to the years of his late maturity, for the Operette morali. About the «Dialoghi» (as he always preferred to mention them), Puccinotti was immediately enthusiastic, revealing an intimate adherence to the profound substance of the text and becoming an active promoter even after having been transferred to the University of Macerata, in January 1826. The importance of this appreciation, sometimes expressed in clear-cut and radical terms, represents a useful testimony in the definition of a first, selected group of ideal readers of the work.